A Review of Mycotoxin Types, Occurrence, Toxicity, Detection Methods and Control: Review: Review of Mycotoxin Types - Zahra, Naseem; Saeed, Muhammad Khalid; Sheikh, Asma; Kalim, Imran; Ahmad, Sajid Rashid; Jamil, Nadia (Biological Sciences - PJSIR, 2019)
Mycotoxins are health hazardous natural toxin produced by various fungal species due to favourable environmental conditions for fungal growth. These are carcinogenic, hepatotoxic and immuno- suppressive substances usually found in food and feed items. Mycotoxins are broadly divided into two major groups on the basis of mycotoxin producing fungi i.e., those fungi which invade in pre-harvest conditions and those which are produced in post-harvest conditions called storage fungi. The conditions which promote mycotoxin growth are high temperatures, moisture levels, poor hygienic conditions and contamination during storage and transportation. Aflatoxins, ochratoxins, citrinin, trichothecene, fumonisins, patulin and zearalenone are prominent mycotoxins in food and feed commodities. This review renders the comprehensive data regarding occurrence of main mycotoxins, their analysis and health hazardous effects on human health alongwith some detoxification protocols.